1983
DOI: 10.1139/v83-229
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interface mass transfer on the liquid-phase oxidation of acetaldehyde

Abstract: Partial oxidation of acetaldehyde by oxygen in the liquid phase was studied in the temperature range from −10 °C to 34 °C, oxygen flow rate from 90 to 100 mL/min, concentration of acetaldehyde from 3.0 to 34.0 volume percent, and at different partial pressures of oxygen. Cobalt acetate was used as catalyst. It was found that the reaction rate was governed by two types of rate equations depending on the operating conditions as well as the loading of catalyst.In the region of higher oxygen mass transfer, the rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…One is similar to the homogeneous liquid phase oxidation of acetaldehyde using Co3+ ions as catalyst. The Co3+ ions initiate the free radicals, and the subsequent reactions to form peroxides are free radical chain reactions in the liquid phase (Chou and Lin, 1980,1982a, 1983; Allen and Aguilo, 1968; Matsuzaki and Imamura, 1975;Takaoka, 1976;Clinton et al, 1975). The other possible reaction mechanism is a typical heterogeneous catalytic reaction.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One is similar to the homogeneous liquid phase oxidation of acetaldehyde using Co3+ ions as catalyst. The Co3+ ions initiate the free radicals, and the subsequent reactions to form peroxides are free radical chain reactions in the liquid phase (Chou and Lin, 1980,1982a, 1983; Allen and Aguilo, 1968; Matsuzaki and Imamura, 1975;Takaoka, 1976;Clinton et al, 1975). The other possible reaction mechanism is a typical heterogeneous catalytic reaction.…”
Section: Methodsmentioning
confidence: 99%
“…Reaction Mechanism I. The liquid-phase oxidation of acetaldehyde to form PAA using homogeneous Co3+ ions as catalyst is a free-radical reaction (Chou and Lin, 1980, 1982a, 1983Clinton et al, 1975). Several investigators found that the exchanged metal ions on the resin or other carriers had catalytic activities and properties similar to those of the homogeneous metal ions (Matsuzaki and Imamura, 1975).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cobalt catalyst is regenerated by decomposing peracetic acid. In kinetic studies [127], CH 3 CO 3 was the main free radical in the liquid phase. Other catalysts, for example phosphomolybdic acids [128], also catalyze acetaldehyde oxidation.…”
Section: Acetaldehyde Processmentioning
confidence: 99%
“…The in situ process is better. The organic peracids can be also synthesized from aldehydes and oxygen by using Co 3+ ion as homogeneous catalyst in the liquid phase (Chou and Lin, 1983). The decompositions of organic peracids were very rapid in liquid solution in the presence of Co 2+ ion (Allen and Aquilo, 1968).…”
Section: Introductionmentioning
confidence: 99%